Kuznets curve with parabola-shaped ultra-wideband antenna with defected ground plane for communications. Issue 3 (17th June 2021) - Konkyana, Lalitha Bhavani; Alapati, Sudhakar
Abstract : Purpose: This paper aims to state the configuration of the proposed antenna which is competent to many networks such as LTE and X band applications. The experimental study encountered the significance of the proposed antenna. Design/methodology/approach: A novel compact Kuznets curve with parabola-shaped quad-band notched antenna is demonstrated in this paper. The presented prototype is ascertained on a composite material composed of woven fiberglass cloth with an epoxy resin binder. The resulting ultra-wideband antenna ranges 3.1–3.54 GHz, 5.17–5.51 GHz, 5.74–6.43 GHz and 6.79–7.60 GHz. To avoid the frequency bands which cause UWB interference, the projected antenna has been incorporated with slotted patch. The proposed antenna design is attained in four steps. The simple circular patch antenna model with defected ground plane is subjected to stepwise progression by including parabola-shaped slot and U shaped slot on the patch to attain four notched bands. Findings: This projected antenna possesses an optimal bond among simulated and measured outcomes, which is more suitable for the quad notched band applications. Substrate analysis is done by varying substrate material, and notch behavior is presented. The proposed method's optimum performance in metrics such as return loss, voltage standing wave ratio and radiation pattern varies its frequency range from 2.56 to 7.6 GHz. Originality/value: The antenna adaptation of the defected ground plane has achieved through the quad notched band with operating frequency ranges 2.56 to 7.6 GHz and with eliminated frequency ranges 3.55–5.16 GHz, 5.52–5.73 GHz, 6.44–6.78 GHz and 7.66–10.6 GHz.